P27/CDKN1B Translational Regulators in Pituitary Tumorigenesis - Martins, C. S.; Camargo, R. C.; Saggioro, F. P.; Neder, L.; Machado, H. R.; Moreira, A. C.; de Castro, M. (Hormone and Metabolic Research, 2016)
In pituitary tumors, P27(CDKN1B) is underexpressed. We aimed to clarify whether translational regulation underlies this phenomenon. This study evaluated the expression of P27/CDKN1B, its targets (CCNE1, CDK2) and translational regulators (DKC1, RPS13, miR221, miR222) and screened for DKC1 variants in sporadic pituitary adenomas. Samples were obtained during transsphenoidal surgery from 48 patients with pituitary adenomas: 10 ACTH-, 17 GH-secreting, and 21 nonfunctioning (NFPA). The control group comprised 7 normal pituitaries (NP) obtained during autopsies. Gene expression was assessed by RT-PCR and protein expression by immunohistochemistry. The 15 exons of DKC1 were sequenced. P27 protein underexpression was observed in all adenomas subtypes (p=0.001). CCNE1 mRNA (p=0.01) overexpression, but not protein, was observed in NFPA. No differential gene expression among groups was observed in CDKN1B regulators RPS13 (p=0.23) and DKC1 (p=0.34). The expression of miR221 and miR222 was similar among tumors and NP. Frequent DKC1 variants (SNPs) were found in exon 14 and in the 3′-UTR in similar frequency to NCBI-dsSNP databases. We also observed rare DKC1 variants in 11% of the studied tumor samples, indicating a high prevalence in pituitary adenomas, however, in silico studies failed to indicate deleterious effects. The high frequency of DKC1 variants may influence, in some extent, pituitary tumors development, without clear role in its tumorigenesis. Our data reinforce the P27 underexpression in pituitary adenomas and provide further evidence of the post-translational machinery involvement, although this phenomenon cannot be explained either by mis-expression of P27 translational regulators – DKC1, RPS13, miR221, miR222 – or directly by DKC1 mutations.
Keywords: cell cycle; anterior pituitary; neoplasia; gene regulation